Electrode assembly, lithium ion battery and electric equipment

By setting the active material layer in the positive and negative electrode sheet of the lithium-ion battery and controlling its specific surface area to match each other, the problem of the inability to accurately regulate the battery's fast charging capability in the prior art is solved, and the high-rate performance, energy density and cycle life of the battery are achieved.

CN119764330APending Publication Date: 2025-04-04BYD CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510014793.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The prior art cannot accurately regulate the fast charging capability of lithium-ion batteries, and cannot predict the relationship between the pole chip and battery performance.

Method used

By limiting the specific surface area of ​​the positive and negative electrode sheets and matching them with each other, the electrochemical reaction of the battery is balanced during charging and discharging. Specific measures include providing an active material layer in the positive electrode sheet and the negative electrode sheet, and controlling its specific surface area between 6-7.5 m2/g and 0.5-1.2 m2/g.

Benefits of technology

It achieves the balance of battery rate performance, energy density and cycle life, and improves the battery's fast charging capability and cycle stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764330A_ABST
    Figure CN119764330A_ABST
Patent Text Reader

Abstract

The invention relates to an electrode assembly, a lithium ion battery and electric equipment. The electrode assembly comprises a positive pole piece and a negative pole piece, the positive pole piece comprises a positive current collector and a positive active material layer arranged on at least one surface of the positive current collector; a positive electrode active material in the positive electrode active material layer comprises lithium iron phosphate; the negative pole piece comprises a negative current collector and a negative active material layer arranged on at least one surface of the negative current collector; a negative electrode active material in the negative electrode active material layer comprises graphite; the BET specific surface area of the positive pole piece is 6-7.5 m < 2 > / g, and the BET specific surface area of the negative pole piece is 0.50-1.20 m < 2 > / g. By limiting the specific surface areas of the positive and negative plates, the specific surface areas of the positive and negative plates are matched with each other, so that the electrochemical reaction of the battery in the charging and discharging process is performed in a balanced manner, and the rate capability, the energy density and the cycle life of the battery are considered.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of batteries, and in particular, relates to an electrode assembly, a lithium-ion battery and an electrical device. Background Art

[0002] As the environmental situation becomes increasingly severe, controlling carbon emissions is an inevitable choice to cope with the challenges of resource scarcity and limited environmental carrying capacity. Under this opportunity, new energy vehicles are developing rapidly, and consumers are increasingly demanding lithium-ion batteries as the power unit of new energy vehicles. Among them, charging time is an important factor that the public considers for new energy vehicles. Major charging networks have also accelerated the layout of fast charging, and battery fast charging technology has become a research hotspot.

[0003] CN117766844A discloses a fast-charge and fast-discharge lithium-ion battery, including a positive electrode sheet, a negative electrode sheet, a diaphragm, and an electrolyte, wherein the specific surface area of ​​the positive electrode active material lithium iron phosphate is 12m 2 / g~17m 2 / g, the specific surface area of ​​artificial graphite, the negative electrode active material, is 1.8m 2 / g~2.1m 2 / g, and the fast charging and discharging of lithium-ion batteries can be achieved by controlling the surface density and compaction density of the positive electrode slurry and the negative electrode slurry.

[0004] However, the existing technology generally only limits the specific surface area of ​​the active material, and is actually unable to predict the relationship between the electrode and the battery performance, and is unable to accurately regulate the fast charging capability of the battery. Summary of the invention

[0005] The purpose of the present invention is to further improve the rate performance, energy density and cycle life of the battery, thereby improving the fast charging capability of the battery.

[0006] In order to achieve the above-mentioned object, the first aspect of the present invention provides an electrode assembly, the electrode assembly comprising a positive electrode sheet and a negative electrode sheet; the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector; the positive electrode active material in the positive electrode active material layer comprises lithium iron phosphate; the negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector; the negative electrode active material in the negative electrode active material layer comprises graphite; the BET specific surface area of ​​the positive electrode sheet is 6-7.5 m 2 / g, and the BET specific surface area of ​​the negative electrode plate is 0.50-1.20 m 2 / g.

[0007] Optionally, the BET specific surface area of ​​the positive electrode plate is 6.5-7 m 2 / g, and the BET specific surface area of ​​the negative electrode sheet is 0.6-1 m 2 / g.

[0008] Optionally, the positive electrode active material includes coarse particles and fine particles; the D50 particle size of the coarse particles is 1-4 μm, and the D50 particle size of the fine particles is 0.1-0.4 μm; the weight ratio of the coarse particles to the fine particles is 1:(0.43-1.5), preferably 1:(0.43-0.67).

[0009] Optionally, based on the weight of the positive electrode active material layer, the content of the positive electrode active material on a dry basis is 85-98 wt %.

[0010] Optionally, the positive electrode active material layer further comprises a positive electrode conductor and a positive electrode binder; based on the weight of the positive electrode active material layer, the content of the positive electrode conductor is 1-5 wt % on a dry basis, and the content of the positive electrode binder is 1-5 wt %.

[0011] Optionally, the positive electrode conductive agent includes one or more of carbon nanotubes, carbon black and graphite microsheets; preferably, the positive electrode conductive agent includes carbon nanotubes, carbon black and graphite microsheets; the weight ratio of the carbon nanotubes, carbon black and graphite microsheets is 1: (4-9): (1-6).

[0012] Optionally, the diameter of the carbon nanotube is 10-25 nm; and / or the particle size of the carbon black is 50-100 nm; and / or the diameter of the graphite microsheet is 0.5-4.5 μm, and the thickness is 5-100 nm.

[0013] Optionally, the compaction density of the positive electrode sheet is 2-2.5 g / cm 3 .

[0014] Optionally, a discontinuous conductive carbon layer is bonded to the surface of the positive electrode current collector; the thickness of the conductive carbon layer is 0.3-1.8 μm; optionally, the conductive carbon layer includes a flaky conductive agent and a binder.

[0015] Optionally, the negative electrode active material in the negative electrode active material layer includes graphite; and the D50 particle size of the negative electrode active material is 3.5-40 μm.

[0016] Optionally, the negative electrode active material layer further includes a negative electrode conductor and a negative electrode binder; based on the total weight of the negative electrode active material layer, the negative electrode active material layer includes 85-98 parts by weight of negative electrode active material, 0.2-5 parts by weight of negative electrode conductor and 1-10 parts by weight of negative electrode binder.

[0017] Optionally, the compaction density of the negative electrode plate is 1.2-1.8 g / cm 3 .

[0018] A second aspect of the present invention provides a lithium ion battery, the lithium ion battery comprising the electrode assembly of the first aspect of the present invention.

[0019] A second aspect of the present invention provides an electrical device, wherein the electrical device comprises the electrode assembly according to the first aspect of the present invention or the lithium ion battery according to the second aspect of the present invention.

[0020] Through the above technical scheme, the present invention limits the specific surface area of ​​the positive and negative electrodes so that the specific surface areas of the positive and negative electrodes match each other, so that the electrochemical reaction of the battery during the charging and discharging process is balanced, which not only increases the contact area between the electrode and the electrolyte, but also avoids an increase in side reactions between the electrolyte and the electrodes, thereby taking into account the battery's rate performance, energy density and cycle life.

[0021] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present invention but do not constitute a limitation of the present invention. In the accompanying drawings: Figure 1 is a SEM image of a positive electrode sheet with a conductive carbon layer on the surface of the positive electrode current collector in some embodiments of the present invention. Figure 1 Box part. DETAILED DESCRIPTION

[0023] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0024] Positive and negative electrode active materials are important components of batteries. Compared with ternary positive electrode active materials, lithium phosphate-containing positive electrode active materials have lower battery energy density, so active materials with high specific surface area are generally used to improve the battery's charge and discharge performance and rate performance. However, the positive electrode active material layer also contains conductive agents and binders, and the specific surface area of ​​the positive and negative electrode sheets is also crucial to the battery performance.

[0025] The first aspect of the present invention provides an electrode assembly, the electrode assembly comprising a positive electrode sheet and a negative electrode sheet; the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector; the positive electrode active material in the positive electrode active material layer comprises lithium iron phosphate; the negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector; the negative electrode active material in the negative electrode active material layer comprises graphite; the BET specific surface area of ​​the positive electrode sheet is 6-7.5 m 2 / g, and the BET specific surface area of ​​the negative electrode sheet is 0.5-1.2 m 2 / g.

[0026] The present invention uses the above technical scheme to match the specific surface areas of the positive and negative electrode sheets, which is beneficial to the balanced electrochemical reaction of the battery prepared from the above electrode assembly during the charging and discharging process, and is beneficial to increasing the rate of the electrochemical reaction. At the same time, it can avoid the irreversible capacity loss caused by the increase of side reactions between the electrodes and the electrolyte, thereby taking into account the charging and discharging performance and cycle life of the battery.

[0027] By controlling the specific surface area of ​​the positive electrode and the negative electrode within an appropriate range, it is beneficial to provide more active sites, thereby increasing the contact area between the electrode and the electrolyte, thereby improving the charge and discharge performance of the battery; the electrode has a suitable specific surface area can reduce the shedding and aggregation of active substances, thereby reducing the performance degradation of the battery during the cycle, reducing the diffusion distance of lithium ions in the electrode, reducing the internal resistance of the battery, and improving the cycle stability of the battery.

[0028] In the present invention, the specific surface areas of the positive and negative electrode sheets are respectively tested by nitrogen adsorption method and calculated by BET method, and the test steps refer to GB / T 19587-2017 gas adsorption BET method for determining the specific surface area of ​​solid substances.

[0029] The inventors of the present invention have found in their research that the specific surface areas of the positive and negative electrodes each have an appropriate specific surface area and match each other, which can improve the charge and discharge performance of the battery and improve the cycle stability of the battery. If the specific surface area of ​​the positive electrode is much larger than that of the negative electrode, the negative electrode may become a bottleneck that limits the battery performance; conversely, if the specific surface area of ​​the negative electrode is too large, it may lead to excessive consumption of the electrolyte and increase in the internal impedance of the battery.

[0030] In some embodiments of the present invention, the BET specific surface area of ​​the positive electrode sheet is 6-7.5 m 2 / g, for example, the specific surface area of ​​the positive electrode sheet can be 6.0 m 2 / g, 6.1 m 2 / g, 6.2 m 2 / g, 6.3 m 2 / g, 6.4 m 2 / g, 6.5 m 2 / g, 6.6 m 2 / g, 6.7 m 2 / g, 6.8 m 2 / g, 6.9 m 2 / g, 7.0 m 2 / g, 7.1 m 2 / g, 7.2 m 2 / g, 7.3 m 2 / g, 7.4 m 2 / g, 7.5 m 2 / g or any value in the above range. In order to further improve the charge and discharge performance and cycle stability of the battery, the BET specific surface area of ​​the positive electrode sheet is preferably 6.5-7 m 2 / g.

[0031] In some embodiments of the present invention, the BET specific surface area of ​​the negative electrode plate is 0.50-1.20 m 2 / g, for example, the specific surface area of ​​the negative electrode sheet can be 0.50 m 2 / g, 0.55 m 2 / g, 0.60 m 2 / g, 0.67 m 2 / g, 0.70 m 2 / g, 0.75 m 2 / g, 0.80 m 2 / g, 0.90 m 2 / g, 0.96 m 2 / g, 1.00 m 2 / g, 1.05 m 2 / g, 1.10 m 2 / g, 1.15 m 2 / g, 1.20 m 2 In order to further improve the charge and discharge performance and cycle stability of the battery, the BET specific surface area of ​​the negative electrode sheet is preferably 0.6-1 m 2 / g.

[0032] In the present invention, the specific surface areas of the positive and negative electrode sheets are respectively within the above ranges, which can make the electrochemical performance of the lithium-ion battery reach a better state. When the specific surface area of ​​the electrode sheet is too large, for example, the BET specific surface area of ​​the positive electrode sheet tested by the nitrogen adsorption method is greater than 7.5 m 2 / g, BET specific surface area of ​​negative electrode BET>1.2 m 2 / g, the side reactions between the electrode and the electrolyte increase, resulting in an increase in the irreversible capacity loss of the battery, affecting the energy density and cycle life of the battery; at the same time, an excessively large specific surface area may cause the volume expansion and contraction of the electrode material to be more significant during the charge and discharge process of the battery, which may cause the material to break and the electrode to fall off, thereby reducing the structural stability of the electrode material. When the specific surface area of ​​the electrode is small, for example, the BET specific surface area of ​​the positive electrode tested by the nitrogen adsorption method is less than 6 m 2 / g, BET specific surface area of ​​negative electrode BET<0.5 m 2 / g, the electrode has fewer active sites, which reduces the contact area between the electrode and the electrolyte, slows down the electrochemical reaction rate, and affects the charge and discharge performance of the battery. At the same time, the diffusion distance of lithium ions in the electrode may increase, resulting in an increase in the internal resistance of the battery.

[0033] In some embodiments of the present invention, the positive electrode active material includes coarse particles and fine particles. The positive electrode active material provided by the present invention has a bimodal distribution of powder particle size, so that the positive electrode active material powder has a suitable tap density, thereby improving the electrochemical performance of the battery.

[0034] In some embodiments of the present invention, the D50 particle size of the coarse particles is 1-4 μm, and the D50 particle size of the fine particles is 0.1-0.4 μm; the weight ratio of the coarse particles to the fine particles is 1:(0.43-1.5), preferably 1:(0.43-0.67). By properly matching the coarse particles and the fine particles, it is beneficial to improve the transmission performance of lithium ions and electrons, and improve the rate performance, cycle life and energy density of the battery.

[0035] In the present invention, the D50 particle size of the positive electrode active material refers to the particle size corresponding to when the cumulative volume distribution percentage of the positive electrode active material reaches 50%.

[0036] In the present invention, the positive electrode active material may be lithium iron phosphate (LiFePO4), which has the advantages of high theoretical capacity and long cycle life, but has low conductivity, which affects its power performance. By doping lithium iron phosphate, its crystal structure may be improved. For example, the element doped to modify lithium iron phosphate may be titanium. In some preferred specific embodiments of the present invention, the positive electrode active material includes titanium-doped lithium iron phosphate.

[0037] In some embodiments of the present invention, the content of titanium is 0.20-0.30 wt % based on the weight of the titanium-doped lithium iron phosphate. By doping lithium iron phosphate with an appropriate amount of titanium, the olivine crystal structure of lithium iron phosphate can be stabilized, the crystal particle size can be prevented from being too large, the lithium ion extraction / embedding path can be shortened, the diffusion rate of lithium ions can be increased, the discharge specific capacity can be increased, and the conductivity of the material can be improved, and the charge and discharge rate and polarization resistance of the battery can be improved.

[0038] In some embodiments of the present invention, the content of the positive electrode active material is 85-98 wt % on a dry basis, based on the weight of the positive electrode active material layer. This is beneficial to improving the charge and discharge rate performance, energy density and cycle stability of the battery.

[0039] In some embodiments of the present invention, the positive electrode active material layer further includes a positive electrode conductor and a positive electrode binder.

[0040] In some embodiments of the present invention, the content of the positive electrode binder is 1-5 wt% on a dry basis based on the weight of the positive electrode active material layer. The positive electrode binder is conducive to the formation of a good conductive network of the positive electrode active material layer and can be dissolved in an organic solvent. In the present invention, the positive electrode binder can be selected from one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE) and fluorine-containing acrylic resin.

[0041] In some embodiments of the present invention, the content of the positive electrode conductive agent is 1-5 wt % on a dry basis based on the weight of the positive electrode active material layer. By controlling the amount of the conductive agent and the binder, the energy density of the battery can be further improved.

[0042] In some embodiments of the present invention, the positive electrode conductive agent includes one or more of carbon nanotubes, carbon black and graphite microsheets.

[0043] In the present invention, the positive electrode conductive agent preferably includes a tubular conductive agent, a granular conductive agent and a flake conductive agent. The tubular conductive agent may be a tubular carbon nanotube or a carbon fiber; the granular conductive agent may be selected from one or more of graphite and carbon black; and the flake conductive agent may be selected from one or more of graphene and graphite microsheets.

[0044] In some preferred embodiments of the present invention, the positive electrode conductive agent includes carbon nanotubes, carbon black and graphite microsheets; the weight ratio of the carbon nanotubes, carbon black and graphite microsheets is 1: (4-9): (1-6). By adding tubular conductive agents, granular conductive agents and sheet conductive agents at the same time and matching them reasonably, it is beneficial to improve the conductivity of the positive electrode active material layer, and it is also beneficial for the binder to bond the conductive agent and the positive electrode active material, thereby ensuring the gram capacity of the positive electrode sheet, thereby improving the energy density of the battery.

[0045] In some embodiments of the present invention, the diameter of the carbon nanotubes (CNTs) is 10-25 nm. By doping the positive electrode material with CNTs material, the bonding strength of the positive electrode plate can be improved, the amount of binder can be reduced, the conductivity of the positive electrode material can be enhanced, and the internal resistance of the lithium battery can be reduced. CNTs can also build a conductive network inside the plate and inside the battery, reduce the expansion and contraction of the active material during charging and discharging, and improve the battery life.

[0046] In some embodiments of the present invention, the particle size of the carbon black is 50-100 nm. The carbon black can be selected from one or more of Ketjen black, acetylene black and conductive carbon black Super P.

[0047] In some embodiments of the present invention, the graphene microplatelet has a diameter of 0.5-4.5 μm and a thickness of 5-100 nm.

[0048] In some embodiments of the present invention, the compaction density of the positive electrode sheet is 2-2.5 g / cm 3 In this way, the amount of active material per unit volume increases, thus improving the energy density of the battery.

[0049] In some embodiments of the present invention, the surface of the positive electrode collector is combined with a discontinuous conductive carbon layer, which can reduce the interfacial impedance between the positive electrode collector and the positive electrode active material and enhance the conductivity; on the other hand, the conductive carbon layer can improve the problem of electrochemical corrosion on the surface of the positive electrode collector, reduce polarization, increase the bonding force between the positive electrode active material layer and the positive electrode collector, and prevent the electrolyte from corroding the positive electrode collector.

[0050] In the present invention, the conductive carbon layer is intermittently distributed on the positive electrode current collector, and can be spot coated so that the conductive carbon layer on the positive electrode current collector is in the form of dots, or can be a segment with a certain width.

[0051] In some embodiments of the present invention, the thickness of the conductive carbon layer is 0.3-1.8 μm.

[0052] Optionally, the conductive carbon layer includes a flake conductive agent and a binder. The specific material of the flake conductive agent may be the same as or different from the material of the flake positive electrode conductive agent, for example, it may be graphite microsheets.

[0053] In the present invention, the negative electrode active material includes graphite, which has a high specific surface area and electrical conductivity, and also has good chemical stability, and can improve the cycle life of the battery. Specifically, the graphite can be selected from one or more of artificial graphite and natural graphite.

[0054] In some embodiments of the present invention, the particle size of the negative electrode active material is 3.5-40 μm. By controlling the particle size, it is beneficial for the negative electrode active material to fully contact with the electrolyte, and when more active sites are provided, the side reactions between the negative electrode active material and the electrolyte are reduced, and the battery rate performance and cycle life are taken into consideration.

[0055] In some embodiments of the present invention, the negative electrode active material layer also includes a negative electrode conductor and a negative electrode binder; based on the total weight of the negative electrode active material layer, the negative electrode active material layer includes 85-98 parts by weight of negative electrode active material, 0.2-5 parts by weight of negative electrode conductor and 1-10 parts by weight of negative electrode binder.

[0056] The negative electrode conductive agent may be selected from one or more of conductive carbon black, acetylene black, Ketjen black, carbon nanotubes, graphene, carbon fiber and conductive graphite. The negative electrode binder may be selected from styrene-butadiene rubber (SBR) and other water-soluble binders, for example, one or more of water-soluble unsaturated resins and water-soluble acrylic resins. A suitable amount of the negative electrode binder is beneficial to improving the capacity and rate performance of the battery.

[0057] In some embodiments of the present invention, an auxiliary agent is further added to the negative electrode active material layer, for example, a thickener such as sodium carboxymethyl cellulose (CMC).

[0058] In the present invention, the D50 particle size of the negative electrode active material refers to the particle size corresponding to when the cumulative volume distribution percentage of the negative electrode active material reaches 50%.

[0059] In some embodiments of the present invention, the compaction density of the negative electrode plate is 1.2-1.8 g / cm 3 .

[0060] By controlling the porosity and compaction density of the negative electrode sheet within a suitable range, it is beneficial to obtain a negative electrode sheet with a suitable BET specific surface area.

[0061] A second aspect of the present invention provides a lithium ion battery, wherein the lithium ion battery comprises the above-mentioned electrode assembly.

[0062] In the present invention, the lithium-ion battery includes the above-mentioned electrode assembly, and also includes a separator and an electrolyte. The separator is provided between the positive electrode sheet and the negative electrode sheet to separate the positive electrode sheet from the negative electrode sheet. The material of the separator can be selected according to demand, for example, it can be a composite material of one or more of polyethylene, polypropylene, polyvinylidene fluoride and polyimide.

[0063] The electrolyte includes a lithium-containing electrolyte salt and a solvent. The lithium-containing electrolyte salt can be selected according to requirements, for example, it can be lithium hexafluorophosphate (LiPF6).

[0064] A third aspect of the present invention provides an electrical device, which includes the aforementioned electrode assembly or the aforementioned lithium-ion battery.

[0065] In the present invention, the electrical equipment includes but is not limited to mobile devices (mobile phones, tablet computers and laptop computers), electric vehicles (pure electric vehicles, hybrid electric vehicles, electric bicycles), and energy storage devices.

[0066] The present invention is further described below in conjunction with embodiments, but the present invention is not limited thereto.

[0067] The raw materials used in the examples can all be obtained through commercial sources.

[0068] The thickness of the positive electrode current collector aluminum foil used in the examples and comparative examples is 13 μm; the thickness of the negative electrode current collector copper foil is 6 μm; and the thickness of the polyethylene film separator is 9 μm.

[0069] The specific surface areas of the positive electrode sheet and the negative electrode sheet in the embodiment are tested by nitrogen adsorption analysis method and calculated by BET method. The test steps refer to GB / T 19587-2017 Gas adsorption BET method for determining the specific surface area of ​​solid substances.

[0070] The electrode used for testing may be a electrode prepared according to the method of the embodiment, or may be a electrode obtained by disassembling a battery.

[0071] Example 1 This embodiment is used to illustrate the method for preparing the electrode assembly of the present invention, comprising the following steps: Preparation of positive electrode sheet: positive electrode active material lithium iron phosphate, positive electrode conductive agent, and binder polyvinylidene fluoride (PVDF) are mixed in a weight ratio of 96:1:3, the mixed powder is mixed with N-methyl-2-pyrrolidone (NMP), and stirred evenly under the action of a homogenizer to obtain positive electrode slurry; the positive electrode slurry is evenly coated on the double-layer surface of the positive electrode current collector aluminum foil, and dried to form a positive electrode active material layer on the surface of the aluminum foil; the dried positive electrode sheet is rolled and cut to obtain a compaction density of 2.0 g / cm 3 The positive electrode sheet after rolling; Among them, lithium iron phosphate includes coarse particles and fine particles. The D50 particle size of the coarse particles is 1 μm, the D50 particle size of the fine particles is 0.1 μm, and the weight ratio of the coarse particles to the fine particles is 4:6; the positive electrode conductive agent includes carbon nanotubes (CNTs), carbon black (Super P) and graphite microsheets in a weight ratio of 1:6:3. The diameter of the carbon nanotubes is 10 nm, the particle size of the carbon black (Super P) is 50nm, the diameter of the graphite microsheets is 0.5 μm, and the thickness is 100 nm.

[0072] Preparation of negative electrode sheet: artificial graphite as negative electrode active material, conductive carbon black Super P, thickener sodium carboxymethyl cellulose (CMC) and binder styrene butadiene rubber latex (SBR) are mixed in a weight ratio of 95:1:1.5:2.5, the mixed powder is mixed with deionized water, and stirred evenly under the action of a homogenizer to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on both sides of the negative electrode current collector copper foil, and dried to form a negative electrode active material layer on the copper foil; the dried electrode sheet is rolled and cut in turn to obtain a compaction density of 1.35 g / cm 3 The negative electrode sheet after rolling.

[0073] Among them, the D50 particle size of artificial graphite is 3.5μm; the D50 particle size of conductive carbon black Super P is 50 nm.

[0074] Example 2 The method for preparing the electrode assembly in this embodiment is basically similar to that in Embodiment 1, except that: Positive electrode: The D50 particle size of coarse particles is 2 μm, and the D50 particle size of fine particles is 0.3 μm; the weight ratio of coarse particles to fine particles is 6:4; The D50 particle size of the negative electrode artificial graphite is 10 μm.

[0075] Example 3 The method for preparing the electrode assembly in this embodiment is basically similar to that in Embodiment 1, except that: Positive electrode: The D50 particle size of coarse particles is 4 μm, the D50 particle size of fine particles is 0.4 μm, and the weight ratio of coarse particles to fine particles is 7:3; The particle size D50 of the negative electrode artificial graphite is 40 μm.

[0076] Example 4 The method for preparing the electrode assembly in this embodiment is basically similar to that in Embodiment 2, except that: The weight ratio of the positive electrode active material lithium iron phosphate, the positive electrode conductor and the binder is 97:1:2.

[0077] Example 5 The method for preparing the electrode assembly in this embodiment is basically similar to that in Embodiment 2, except that: The diameter of the carbon nanotubes in the positive electrode conductive agent is 20 nm, and the diameter of the graphite microsheets is 4 μm.

[0078] Example 6 The method for preparing the electrode assembly in this embodiment is basically similar to that in Embodiment 2, except that: The D50 particle size of the artificial graphite, the negative electrode active material, is 8 μm.

[0079] Example 7 The method for preparing the electrode assembly in this embodiment is basically similar to that in Embodiment 2, except that: The D50 particle size of the artificial graphite, the negative electrode active material, is 20 μm.

[0080] Example 8 The method for preparing the electrode assembly in this embodiment is basically similar to that in Embodiment 2, except that: The weight ratio of the negative electrode active material artificial graphite, the negative electrode conductive agent, the thickener and the binder is 96:1:1:2.

[0081] Example 9 The method for preparing the electrode assembly in this embodiment is basically similar to that in Embodiment 2, except that: The positive electrode active material includes titanium-doped lithium iron phosphate, and the Ti doping amount in the titanium-doped lithium iron phosphate is 2700 ppm.

[0082] Example 10 The method for preparing the electrode assembly in this embodiment is basically similar to that in Embodiment 1, except that: The method also includes: before coating the positive electrode slurry on the positive electrode collector, spot coating on the positive electrode collector to form a discontinuous conductive carbon layer, the conductive carbon layer includes graphite microsheets and a binder PVDF, the content of graphite microsheets in the conductive carbon layer is 70wt%; the thickness of the conductive carbon layer is 0.5 μm.

[0083] Embodiment 11 The method for preparing the electrode assembly in this embodiment is basically similar to that in Embodiment 10, except that: The thickness of the conductive carbon layer is 0.3 μm.

[0084] Example 12 The method for preparing the electrode assembly in this embodiment is basically similar to that in Embodiment 10, except that: The thickness of the conductive carbon layer is 1.8 μm.

[0085] Comparative Example 1 The preparation method of the electrode assembly in this comparative example is basically similar to that in Example 1, except that the weight ratio of the coarse particles to the fine particles in the positive electrode active material is 12:8, so that the specific surface area of ​​the positive electrode sheet is 5.0 m 2 / g.

[0086] Comparative Example 2 The preparation method of the electrode assembly in this comparative example is basically similar to that in Example 1, except that the weight ratio of the coarse particles to the fine particles in the positive electrode active material is 9:1, so that the specific surface area of ​​the positive electrode sheet is 8.0 m 2 / g.

[0087] Comparative Example 3 The preparation method of the electrode assembly in this comparative example is basically similar to that in Example 1, except that: the particle size of the negative electrode active material graphite is 2 μm; the specific surface area of ​​the negative electrode sheet is 1.40 m 2 / g.

[0088] Comparative Example 4 The preparation method of the electrode assembly in this comparative example is basically similar to that in Example 1, except that: the particle size of the negative electrode active material graphite is 50 μm; the specific surface area of ​​the negative electrode plate is 0.46 m 2 / g.

[0089] The compaction density analysis was performed on the positive electrode sheets and the negative electrode sheets in Examples 1-12 and Comparative Examples 1-4. The results are shown in Table 1.

[0090] Pole piece specific surface area test: The specific surface area of ​​the positive electrode pieces and negative electrode pieces obtained in Examples 1-12 and Comparative Examples 1-4 was tested by nitrogen adsorption method, and calculated by BET method. The results are shown in Table 1.

[0091] The electrode assemblies obtained in the embodiment and the comparative example were respectively assembled into corresponding lithium-ion batteries.

[0092] Preparation of lithium-ion batteries: stack the positive electrode sheet, polyethylene film separator, and negative electrode sheet in order, so that the separator separates the positive electrode sheet from the negative electrode sheet, and then wind the stacked materials to obtain a bare cell; place the bare cell in an outer packaging shell, inject electrolyte after drying, and obtain a battery through vacuum packaging, standing, forming, shaping and other processes.

[0093] The electrolyte is prepared according to the following method: ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain a mixed organic solvent; dry lithium salt LiPF6 is dissolved in the organic solvent to prepare an electrolyte with a concentration of 1 mol / L.

[0094] Performance Testing 1. Battery DC internal resistance test The battery DC internal resistance test was conducted on the battery assembled with the electrode assemblies obtained in the embodiment and the comparative example. The test method included: discharging the battery at room temperature at a constant current of 0.33 C (0.6 A) with a cut-off voltage of 2.0 V, and then charging it at 0.33 C to 50% SOC (charging capacity 0.9 A). The voltage at this time was the pre-discharge voltage V0. Using 1.5 C (i.e., discharge current I i The battery was discharged at a constant current of 2.7A for 30 s, and the discharge voltage V at the 30th s was recorded. i. Calculate the discharge DC internal resistance DCIR according to the following formula: DCIR (mΩ) = (V0-V i ) / I i *1000.

[0095] The current internal resistance test results of the battery are shown in Table 1.

[0096] 1. Battery cycle performance test The battery prepared by the electrode assembly obtained in the embodiment and the comparative example was subjected to a battery cycle performance test, and the test method included: (1) At 25°C, the battery was charged at a constant current of 0.5 C to 3.65 V, and at a constant voltage of 3.65 V. The cut-off current charging rate was 0.05 C (100% SOC), and then discharged at 0.2 C to 2.2 V to obtain the initial capacity, and then left for 0.5 h. (2) At 25°C, the battery in step (1) was charged to 3.65 V at a charge rate of 1C, left for 0.5 h, and then discharged to 2.2 V at a charge rate of 1C, left for 0.5 h; (3) Repeat step (2) until the capacity of the lithium-ion battery decays to 80% of the initial capacity and record the number of cycles.

[0097] The battery cycle performance test results of the battery are shown in Table 1.

[0098] Table 1

[0099] It can be found from the data in the above table that the battery prepared by the electrode assembly provided by the present invention has lower charge and discharge performance and better cycle stability.

[0100] From the results in Table 1, it can be seen that Comparative Examples 1-2 do not meet the BET specific surface area of ​​the positive electrode sheet of 6-7.5 m 2 / g, and Comparative Examples 3-4 do not meet the BET specific surface area of ​​the negative electrode sheet of 0.5-1.2 m 2 / g, it is impossible to take into account both the charge and discharge performance and cycle life of the battery.

[0101] Based on the test results of Examples 1-8, it can be seen that when the specific surface area of ​​the positive electrode sheet and the specific surface area of ​​the negative electrode sheet match each other, it is beneficial to the balanced electrochemical reaction of the battery prepared by the electrode assembly during the charge and discharge process, thereby improving the charge and discharge performance and cycle life of the battery.

[0102] The preferred embodiments of the present disclosure are described in detail above; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.

[0103] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.

[0104] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.

Claims

1. An electrode assembly, characterized in that: The electrode assembly comprises a positive electrode sheet and a negative electrode sheet; the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector; the positive electrode active material in the positive electrode active material layer comprises lithium iron phosphate; the negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector; the negative electrode active material in the negative electrode active material layer comprises graphite; The BET specific surface area of ​​the positive electrode sheet is 6-7.5 m 2 / g, and the BET specific surface area of ​​the negative electrode plate is 0.50-1.20m 2 / g.

2. The electrode assembly according to claim 1, wherein: The BET specific surface area of ​​the positive electrode sheet is 6.5-7 m 2 / g, and the BET specific surface area of ​​the negative electrode plate is 0.6-1 m 2 / g.

3. The electrode assembly according to claim 1, wherein: The positive electrode active material includes coarse particles and fine particles; The D50 particle size of the coarse particles is 1-4 μm, and the D50 particle size of the fine particles is 0.1-0.4 μm; the weight ratio of the coarse particles to the fine particles is 1:(0.43-1.5), preferably 1:(0.43-0.67).

4. The electrode assembly according to claim 1, wherein: Based on the weight of the positive electrode active material layer, the content of the positive electrode active material is 85-98 wt % on a dry basis.

5. The electrode assembly according to any one of claims 1 to 4, wherein: The positive electrode active material layer also includes a positive electrode conductor and a positive electrode binder; Based on the weight of the positive electrode active material layer, the content of the positive electrode conductor is 1-5 wt % on a dry basis, and the content of the positive electrode binder is 1-5 wt %.

6. The electrode assembly according to claim 5, wherein: The positive electrode conductive agent includes one or more of carbon nanotubes, carbon black and graphite microsheets; Preferably, the positive electrode conductive agent comprises carbon nanotubes, carbon black and graphite microsheets; the weight ratio of the carbon nanotubes, carbon black and graphite microsheets is 1:(4-9):(1-6).

7. The electrode assembly according to claim 6, wherein: The diameter of the carbon nanotubes is 10-25 nm; and / or The particle size of the carbon black is 50-100 nm; and / or The graphite microsheet has a sheet diameter of 0.5-4.5 μm and a sheet thickness of 5-100 nm.

8. The electrode assembly according to claim 1, wherein: The compaction density of the positive electrode sheet is 2-2.5 g / cm 3 .

9. The electrode assembly according to claim 1, wherein: The surface of the positive electrode current collector is combined with a discontinuous conductive carbon layer; The thickness of the conductive carbon layer is 0.3-1.8 μm; Optionally, the conductive carbon layer includes a flake conductive agent and a binder.

10. The electrode assembly according to claim 1, wherein: The negative electrode active material in the negative electrode active material layer includes graphite; The D50 particle size of the negative electrode active material is 3.5-40 μm.

11. The electrode assembly according to claim 10, wherein: The negative electrode active material layer also includes a negative electrode conductor and a negative electrode binder; Based on the total weight of the negative electrode active material layer, the negative electrode active material layer includes 85-98 parts by weight of negative electrode active material, 0.2-5 parts by weight of negative electrode conductor and 1-10 parts by weight of negative electrode binder.

12. The electrode assembly according to claim 1, wherein: The compaction density of the negative electrode plate is 1.2-1.8 g / cm 3 .

13. A lithium ion battery, characterized in that: The lithium-ion battery comprises the electrode assembly according to any one of claims 1 to 12.

14. An electrical device, characterized in that: The electrical equipment comprises the electrode assembly according to any one of claims 1 to 12 or the lithium ion battery according to claim 13.

Citation Information

Patent Citations

  • Rechargeable lithium battery

    CN107039679A

  • Negative electrode piece and secondary battery

    CN109494349A

  • Lithium ion battery

    CN112635822A

  • Lithium ion battery and electric device

    CN114497698A

  • Secondary battery and electric device

    CN115579505A